INVENTORY OF CELASTRACEAE (PARUPUK-PARUPUKAN) SPECIES BASED ON HERBARIUM SPECIMENS OF ANDALAS UNIVERSITY (ANDA) - Ikhsan, Muhammad; Nurainas, Nurainas; Syamsuardi, Syamsuardi (Jurnal Biologi Universitas Andalas, 2025)
Celastraceae has various benefits. However, research on the identification and distribution of Celastraceae species, particularly in Sumatra, is still limited. Therefore, further studies are needed on the identification and distribution of Celastraceae in Sumatra. The Herbarium of Universitas Andalas (ANDA) has a collection of Celastraceae specimens, most of which have not been identified to the species level. Given the high diversity of flora in Indonesia, especially in Sumatra, identifying Celastraceae species is an important step to better understand the potential of these plants. This study aims to determine Celastraceae species and their distribution based on specimens from Herbarium ANDA, which is expected to enrich scientific knowledge about biodiversity in Indonesia and open up opportunities for further utilization of the Celastraceae family. The method used is herbarium-based, involving the management of specimens from Herbarium ANDA. This study identified fifteen species from six genera: Celastrus, Euonymus, Glyptopetalum, Lophopetalum, Microtropis, and Salacia. The distribution of Celastraceae plants in Herbarium ANDA covers West Sumatra, North Sumatra, Riau, and one species from Kagoshima Prefecture, Japan. Most specimens are from West Sumatra, with the distribution detailed as follows: seven species from Padang; two species each from Solok, Lima Puluh Kota, Pasaman, and Mentawai; and one species from Agam and Pasaman Barat. In Riau Province, two species were found in Kampar, and in North Sumatra Province, one species was found in South Tapanuli.Keywords:Â  Celastraceae, Distribution, Inventory, Species.